Discreet and distinct clustering of five model membrane proteins revealed by single molecule localization microscopy. (February 2015) - Magenau, Astrid; Owen, Dylan M.; Yamamoto, Yui; Tran, Jason; Kwiatek, Joanna M.; Parton, Robert G.; Gaus, Katharina
Abstract Compartmentalization is a functionally important property of the plasma membrane, yet the underlying principles that organize membrane proteins into distinct domains are not well understood. Using single molecule localization microscopy, we assessed the clustering of five model membrane proteins in the plasma membrane of HeLa cells. All five proteins formed discrete and distinct nano-scaled clusters. The extent of clustering of the five proteins, independent of their membrane anchors, increased significantly when the fluorescent protein mEOS2 was employed, suggesting that protein–protein interactions are a key driver for clustering. Further, actin depolymerization or reduction of membrane order had a greater, and in some instances opposing effects on the clustering of membrane proteins fused to mEOS2 compared to PS-CFP2-fusion proteins. The data propose that protein interactions can override the lateral organization imposed by membrane anchors to provide an exquisite regulation of the mosaic-like compartmentalization of the plasma membrane.